Cover Image, Volume 33, Issue 5. Issue 5 (1st October 2018) - Silva, Ana P.; Voss, Hans‐Peter; van Zyl, Hannelize; Hogg, Tim; de Graaf, Cees; Pintado, Manuela; Jager, Gerry
Abstract : The cover image, by Ana P. Silva et al., is based on the Original Article Temporal dominance of sensations, emotions, and temporal liking measured in a bar for two similar wines using a multi‐sip approach, https://doi.org/10.1111/joss.12459 .